Dynamic changes of psychrotrophic bacterial populations in Algerian refrigerated raw cow milk - BOUCHAIR, K; BOUBENDIR, A; SERRER, A (Journal of the Hellenic Veterinary Medical Society, 2021)
The aim of the present study is to evaluate the microbial dynamic changes in raw cow milk during refrigeration. Milk samples were collected from two dairy farms situated in basin and mountain areas in the region of Mila, Algeria. Cold storage of milk samples at 4 °C was used to promote psychrotrophic microbial growth during 10 days. The microbial flora of milk was determined by culture methods and the identification of bacterial isolates was carried using cultural, morphological and biochemical criteria. The variations in total viable count and kinetic parameters of microbial growth were analyzed during refrigeration using Baranyi and Roberts Model. The initial microbial counts ranged from 2.94 ±0.04 to 3.87 ±0.11 log CFU * mL-1 and the maximum growth did not exceed 7.00 ±0.12 log CFU * mL-1. The hygienic limit was surpassed after 2 days in the basin farm and later after 6 days in mountain farm. The generation time varied from 1.20 ±0.55 to 4.18 ±0.22 days in the basin farm and mountain farm respectively. The psychrotrophic bacterial populations were identified as Acinetobacter, Pseudomonas, Aeromonas, Chryseobacterium, Enterococcus and Lactobacillus. The notable delay in microbial growth in milk from the mountain farm compared to the one from basin could be related to indoor/outdoor feeding mode adopted in mountain opposed to indoor feeding in the basin farm. This prolonged shelf-life suggests the possible presence of antimicrobial molecules coming from plants grazed around the farm and the selection in the microbiota of some microbial species with antagonist potential.